거주 후 평가를 통한 국가지정 입원치료병상 시설 개선 방향 도출에 관한 연구 - 정다운; 권순정 (의료·복지 건축, 2021)
Purpose: The negative pressure isolation ward is a key facility in preparedness and response to infectious diseases. For the sustainable operation of the facility, appropriate facility improvement is required. The experience of medical staff responding to infectious diseases in the COVID-19 pandemic provides effective informations for facility planning. Methods: The post occupancy evaluation (POE) was conducted by interviewing medical staff who is working on Nationally designated negative pressure isolation ward in general hospital. Floor plan analysis was conducted before field surveys for identifying facility characteristic and spatial composition. After that, field surveys were conducted at 3 hospitals, and interviews and fieldwork were conducted together. Results: It is necessary to increase the standard size of ward area from 15㎡ to 20㎡. The size of the doffing room has to be planned for accommodation of two or more people. Equipment storage, clean storage and waste storage also should be properly planned. There were almost no problems with the circulation in the ward. There was not enough space for medical staff. Implications: For a sustainable and safe negative pressure isolation ward planning, it is necessary to exploit learning from the medical staffs who have many experiences of coping with infectious diseases.
Keywords: Nationally designated negative pressure isolation ward; Post occupancy evaluation(POE); Infectious disease facility; Negative pressure isolation ward; Facility improvement; 국가지정입원치료병상; 거주 후 평가; 감염병시설; 음압격리병동; 시설 개선